Population figures, gender distribution, patterns of settlement and migration in area of the Karmsund strait and Stavanger in the second half of the nineteenth century - Tysdal, Olav (Cogent social sciences, 2017)
This paper concerns population development in the coastal districts near Stavanger County (from 1919, the County of Rogaland) in the second half of the nineteenth century. Its objective is to throw light on relationships between population patterns and the development of commerce: the search for a livelihood being a primary motivating factor in people’s choices of where to live. The study seeks to provide clear answers to questions relating to population developments in the area studied here. The collapse of spring herring fishing early in the 1870s and the crisis that struck the shipping industry in the 1880s had—both separately and together—serious consequences for population development in the areas around the Karmsund strait and Stavanger. Strong population growth came to an end. Emigration, which was sensitive to business cycles, grew substantially, bringing population growth to a virtual halt and simultaneously affecting its structure. Both internal migration and emigration from the country changed the pattern of settlement in Norway.